Velocity Selective Polarization Spectroscopy for Modulation-Free Dispersion Signals at Detuned Frequencies - Yu, Hoon; Kim, Seung Jin; Kim, Jung Bog (Journal of Spectroscopy, 2014)
We present a simple technique to obtain modulation-free locking signals at the detuned frequency from an atom transition between hyperfine structures. Polarization spectroscopy allows us to obtain the dispersion signals that are suitable for frequency locking. Velocity selective optical pumping using another laser beam also allows us to obtain signals at the detuned frequency and to shift crossover signal away. By combining these two techniques, we were able to obtain the velocity selective birefringence signal only at the principle transition in an Rb vapor cell and compare the birefringence signal with the theoretical spectrum predicted by using Nakayama’s model.